Reconstructing Islamic Intellectual Traditions in Modern Scholarship: Textual Hermeneutics, Historical Context, and Epistemological Transformation - Tetiana Kolomoiets; Yevhen Leheza (Fakultas Syariah UIN Antasari, 2026)
Contemporary Islamic scholarship is undergoing a major transformation as it navigates tensions between preserving classical traditions and adapting to modern contexts. This shift reflects both growing epistemological pluralism and an urgent need for methodological reconstruction. Scholars seek to integrate historical consciousness with contemporary frameworks while maintaining doctrinal fidelity through approaches such as neo-ijtihad and contextual hermeneutics. This study examines how Islamic intellectual traditions can remain rigorous, historically grounded, and contextually relevant. It focuses on the methodological gap between classical jurisprudence and modern hermeneutical practices. The research aims to map the evolution of interpretive methodologies, analyze shifts in textual interpretation, and identify epistemological frameworks that support reconstruction. A qualitative approach is employed, using textual hermeneutics, comparative analysis, and historical-contextual examination. Primary sources include classical jurisprudential works and modern interpretations, while secondary sources consist of academic literature. Data analysis is conducted through thematic coding and cross-textual comparison. The findings show that reconstruction occurs through methodological innovation, integration of historical awareness, and acceptance of epistemological pluralism. Contemporary approaches synthesize traditional jurisprudence with modern knowledge systems. In conclusion, Islamic intellectual traditions demonstrate adaptive capacity through creative engagement with their inherent flexibility. Strengthening collaborative ijtihad, interdisciplinary training, and evaluative frameworks is essential for addressing contemporary ethical, legal, and social challenges.